2017
DOI: 10.1080/10641963.2017.1288736
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antihypertensive drugs on breast cancer risk in female hypertensive patients: Evidence from observational studies

Abstract: This systematic review aimed to evaluate the association between antihypertensive drugs and risk of breast cancer, and provide therapeutic implications for female hypertensive patients with different physical appearance. The prevalence of hypertension and female breast cancer is on the rise with age. It has been suggested that ARBs (angiotensin receptor blockers), ACEi (angiotensin-converting enzyme inhibitor), CCBs (calcium channel blockers), and BBs (beta-blockers) were widely used in hypertensive patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
2
20
0
1
Order By: Relevance
“…Our meta-analysis showed a positive association between CCBs use and the risk of breast cancer, which was consistent with the results of previous studies ( Wright et al, 2017 ; Busby et al, 2018a ). The elevated levels of cytosolic calcium could affect the process of apoptosis through different signaling pathways such as caspase activation, induction of endonuclease activity, or the miRNA-524-5p-BRI3-extracellular signal-regulated kinase (Erk) pathway ( Iwasawa et al, 2011 ; Guo et al, 2014 ; Zhao et al, 2017b ). CCBs blocks calcium entry, inhibiting this vital process, which could destroy the body’s natural defense mechanism against cancer growth and promote cell survival by initiating autophagy ( Sun et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis showed a positive association between CCBs use and the risk of breast cancer, which was consistent with the results of previous studies ( Wright et al, 2017 ; Busby et al, 2018a ). The elevated levels of cytosolic calcium could affect the process of apoptosis through different signaling pathways such as caspase activation, induction of endonuclease activity, or the miRNA-524-5p-BRI3-extracellular signal-regulated kinase (Erk) pathway ( Iwasawa et al, 2011 ; Guo et al, 2014 ; Zhao et al, 2017b ). CCBs blocks calcium entry, inhibiting this vital process, which could destroy the body’s natural defense mechanism against cancer growth and promote cell survival by initiating autophagy ( Sun et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results did not explicitly support a bene t of antihypertensive medications for the prognosis of NPC patients treated with IMRT. Previous study results suggested a potential favourable prognostic role of β-blockers for several tumours [25][26]. Moreover, a meta-analyse found that bevacizumab-induced hypertension may represent a prognostic factor in patients with metastatic colorectal cancer [27].…”
Section: Discussionmentioning
confidence: 96%
“…Our previous meta-analysis found a close relationship between hypertension, antihypertensive drugs, and breast cancer (18). The incidence of hypertension in patients with breast cancer increases with age.…”
Section: Literature Search Methodsmentioning
confidence: 92%